2005
DOI: 10.1007/s11139-005-1870-9
|View full text |Cite
|
Sign up to set email alerts
|

On the Maximal Multiplicity of Parts in a Random Integer Partition

Abstract: We study the asymptotic behavior of the maximal multiplicity µ n = µ n (λ) of the parts in a partition λ of the positive integer n, assuming that λ is chosen uniformly at random from the set of all such partitions. We prove that πµ n /(6n) 1/2 converges weakly to max j X j /j as n → ∞, where X 1 , X 2 , . . . are independent and exponentially distributed random variables with common mean equal to 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…(We refer the reader e.g. to [23], [24], [25], [6], [7], [18], [11], [15] and the references therein.) To this effect, Theorem 1 continues the study of partitions initiated by the probabilistic approach.…”
Section: Introductionmentioning
confidence: 99%
“…(We refer the reader e.g. to [23], [24], [25], [6], [7], [18], [11], [15] and the references therein.) To this effect, Theorem 1 continues the study of partitions initiated by the probabilistic approach.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Brennan, Knopfmacher and the author [3] showed that the number of ascents of at least a given size d follows a Gaussian law. The longest run (or largest ascent), however, has a quite unusual and interesting distribution, as recently shown by Mutafchiev [14]-the corresponding distribution function is closely related to the function that generates partitions. Finally, another recent paper by Grabner and Knopfmacher [9] that discusses various partition statistics based on gaps deserves to be mentioned.…”
Section: Introductionmentioning
confidence: 72%
“…It was noted in Mutafchiev's paper [14] that Theorem 5 implies weak convergence of the distribution of the normalized random variable "longest run in a random partition of n" to the distribution of the random variable…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations